Multiperiodic Solution of a Boundary-Value Problem for one Class of Parabolic Equations with Multidimensional Time - Abdikalikova, G. A.; Berzhanov, A. B.; Kenzhebaev, K. K. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the existence and uniqueness of the multiperiodic solution of the first boundary-value problem for a system of parabolic equations with multidimensional time.